NEGATIVE COPULA OF BEING AMONG THE PERSPECTIVES OF HEIDEGGER’S PROJECT OF RADICAL ONTOLOGY - Zakhlypa , Daria (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2022)
Being needs a rectification, that is the compensation of being for Being, which was only assumed, but not substantiated by reason of the influence of the logical fallacy petitio principii and due to the loss of the absolute status of the verb to be from the Greek times to Heidegger’s project of ontology. The annulment of the Greek status of the verb to be caused an absolute disorientation of being regarding its own object and method of action, which ultimately led to the indifference of the ontological background as such. As a result, being did not turn into the smallest semantic unit, like the active parts of speech, but its semantic content expanded to infinity in an eclectic manner, and therefore, being eventually lost the autonomy and limits of its own phenomenological manifestation. This article, which is a part of a larger study at the same time, is based on the idea that negativity is presented as an original characteristic of being in the very first of the judgments about being, namely being is. It turns out that being exists, but only within the utterance, while it is not directly presented, what means it is deprived with predicative features peculiar to it exclusively, except for such one: being is/exists (but) not (only) as something or being is not (only) as something. The aim of the article is to define the negative copula of being as the subject of Heidegger’s project of radical ontology, only sketched in the Marburg lectures of 1927. Besides, the current revival of scientific interest in the direction of subjectivity and spatial localizations of Nothing requires the confirmation of its being-nature, that logically follows from acquisition of the negativity-feature by being-copula, and then –the interpreting of negation as a solely ontological mode of action among the perspectives of the transition to a new beginning, which occupied all scientific research of Heidegger’s later thought. In view of the above, the relevance of copula-studies is only increasing.